No chemical change during high-T dehydration and re-hydration reactions: Constraints from Erzgebirge HP and UHP eclogite - Schmädicke, Esther; Will, Thomas M. (Lithos, 2021)
Meta-basaltic eclogite occurs in the Erzgebirge in three high-pressure (HP) units (Unit 1, 2, and 3) as numerous lenses within high-grade felsic rocks. Units 2 and 3 are common HP units with quartz eclogite, and Unit 1 is an ultra-high pressure (UHP) unit with coesite eclogite, garnetite (metarodingite) and garnet peridotite. The conditions of peak metamorphism increase from Unit 3 (600–650 °C, 20–22 kbar), to Unit 2 (670–730 °C, 24–26 kbar) and Unit 1 (840–920 °C, ≥30 kbar), correlating with a decreasing abundance of hydrous minerals (from >10 vol% in Unit 3 to 0 vol% in Unit 1). In all units, the dominating eclogite type is dark-colored with a composition typical of MORB. A subordinate light type is chemically more variable and has higher contents of Mg, Al, Ca, Cr, Ni, and large ion lithophile elements as well as lower Fe, Zr, Y, and rare earth element concentrations than dark eclogite. Light eclogite formation is interpreted by plagioclase accumulation in a MOR magma chamber. No compositional difference is visible between well-preserved eclogite and samples with variable degrees of post-eclogitic overprint. In addition, dark eclogite from all units is compositionally indistinguishable, implying that prograde dehydration reactions did not modify major and trace element concentrations. This conclusion applies to all reactions in the temperature interval between c. 600 °C (peak T in Unit 3) and c. 900 °C (peak T in Unit 1), including prograde breakdown of calcic amphibole, zoisite, paragonite, and phengite. Together with previous studies on dehydration reactions in blueschist and eclogite at <600 °C (Spandler et al., 2003; Spandler et al., 2004), the present results imply that de-volatilization of the basaltic portion of subducting slabs plays only a minor, if any, role for the enrichment of fluid-mobile elements in the mantle wedge. We infer that most, if not all, of the H2O produced by dehydration reactions between 600 and 900 °C is preserved in eclogite due to the pressure-enhanced capability of garnet and omphacite to incorporate structural water. Incorporation of H2O, produced during the final dehydration stage (c. 800 ± 50 °C, 25–30 kbar), in nominally anhydrous minerals may explain why partial melting obviously did not occur in eclogite.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Eclogite; Element mobility; Erzgebirge; Geochemistry; Mantle wedge; Meta-basalt